Strategi Humas SSC Kacapiring Surabaya Dalam Era Digitalisasi Pada Pandemi Covid-19 - Vaneysa Putri Riduwan; Dyva Claretta (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2022)
Â Technology has become part of humanâ€™s lives, not only to keep up with the times but also as the use of technology that can provide effectiveness and efficiency in doing a job, especially in the era of the Covid-19 pandemic where all of the activities that should be carried out outside the home must be carried out inside home for a while. Such as the case in the education sector. Any kind of learning that takes place outside will have to be done via virtual technology for a while